Accounting choice in troubled companies - DeAngelo, Harry; DeAngelo, Linda; Skinner, Douglas J. (Journal of Accounting and Economics, 1994)
This paper studies accounting choice in 76 NYSE firms with persistent losses and dividend reductions (40% forced by binding covenants). We find that managers' accounting choices primarily reflect their firms' financial difficulties, rather than attempts to inflate income. Firms with and without binding covenants exhibit minor accrual differences in the ten years before the dividend reduction. In the dividend reduction and following three years, the full sample exhibits large negative accruals that likely reflect the fact that 87% of sample firms engage in contractual renegotiations -with lenders, unions, government, and/or management-that provide incentives to reduce earnings.